The use of peer role-play in doctor-patient communication skills training for medical students: A systematic review - Bella Stevanny; Rizma Adlia Syakurah (Institute of Advanced Engineering and Science, 2022)
The quality of communication is directly related to patient satisfaction and can influence health outcomes. However, most doctors still have poor communication skills. A systematic literature search in PubMed, Cochrane, and Science Direct was conducted to retrieve studies reporting the use of peer role-play (PRP) for doctor-patient communication skills training in medical students. The quality of each study was assessed using the Joanna Briggs Institute (JBI) critical appraisal checklist. A total of 1,620 studies were obtained from electronic database search and screening of reference lists. After removing irrelevant studies and duplicates, one randomized control trial (RCT) and eight quasi-experimental studies were included in this systematic review. Peer role-play was perceived to be as useful as simulated patients (SP) training methods with comparable post-intervention objective structured clinical examination (OSCE) scores. Majority of students preferred PRP for learning communication skills over didactic lectures. The limitation of this review is the scarcity of eligible studies, high variability in the PRP programs across studies, and the lack of grey literature included. Peer role-play might be a cost-effective method to improve doctor-patient communication skills with comparable results (student’s perception and OSCE scores) with the expensive use of simulated patients. However, further study is needed to support this statement.